1988
DOI: 10.1079/bjn19880037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrate and its reduction products on the growth and activity of the rumen microbial population

Abstract: 1. The nature of the digestion-inhibiting substance in Kikuyu grass (Pennisetum clandestinum, Hochst), containing high levels of nitrate, was investigated using in vitro digestibility techniques.2. Nitrite, which accumulated during the reduction of nitrate to ammonia, seemed to be the primary factor reducing digestibility. Nitrate and ammonia did not affect digestion in vitro.3. Nitrite caused a reduction in the cellulolytic, xylanolytic and total microbial population, with a concomitant reduction in cellulase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
2
4

Year Published

1990
1990
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 38 publications
4
61
2
4
Order By: Relevance
“…The value obtained in group NS was consistent with the report that the addition of sulfur to the ration did not affect the ammonium level of the rumen (21). It was reported that the extent to which the bacteria reduce nitrite to ammonia may be reduced if the level of ammonia in the rumen is high (22). Taking this situation into account, the fact that the groups do not have any differences with respect to ammonium nitrogen suggests that the level at which nitrite is reduced to ammonium is low since the bacteria meet their required level of ammonium nitrogen.…”
Section: Discussionsupporting
confidence: 94%
“…The value obtained in group NS was consistent with the report that the addition of sulfur to the ration did not affect the ammonium level of the rumen (21). It was reported that the extent to which the bacteria reduce nitrite to ammonia may be reduced if the level of ammonia in the rumen is high (22). Taking this situation into account, the fact that the groups do not have any differences with respect to ammonium nitrogen suggests that the level at which nitrite is reduced to ammonium is low since the bacteria meet their required level of ammonium nitrogen.…”
Section: Discussionsupporting
confidence: 94%
“…2, feed intake was reduced with increasing levels of dietary nitrate. This may be explained by a suppressive effect of nitrite on NDF digestion in the rumen (Marais et al, 1988). Overall, the degree to which feed intake is decreased may depend on the type of diet: DMI of diets containing a greater proportion of NDF appears to be more negatively affected than DMI of high concentrate diets (Lichtenwalner et al, 1973).…”
Section: Effects Of Nitrate On Animal Performancementioning
confidence: 99%
“…The decreased digestibility of crude fibre may be due to the significant (P<0.01) reduction in the caecal bacterial population (Table 4), since the conversion of nitrate to nitrite and nitric oxide has a potential (SPEARS et al, 1977;MARAIS et al, 1988;BAIMATOV, 1991;XU and VERSTRAETE, 2001). …”
Section: Digestibility Nutritive Values and Caecal Bacterial Countmentioning
confidence: 99%